No effect of actual parasitism risk on egg rejection in two sympatric breeding cuckoo hosts - Hanlin Yan (19840763) (2025)
Sifangtuozi Farm (46°00′–46°22ʹ N, 123°46ʹ–123°57ʹ E) is located in the Nenjiang River basin, a tributary of the Songhua River, Jilin Province, southeastern China. The area is characterized by abundant water resources and dense growths of reeds and cattails. Extensive stands of cattails and reeds can be found in different areas surrounding the farm, including field dykes, irrigation channels, streams, and ponds (Trnka et al. 2023). In our study area, ORWs, BRWs and CCs are all summer migrant (Liu et al. 2025). Both ORWs and BRWs mainly inhabit and breed in the riparian vegetation bordering lakes, rivers, and reservoirs, along with marshes and farmlands and reedbeds and plant thickets in the vicinity of water bodies. ORW has been identified as a primary host of CCs, with rates of parasitism ranging from 34.3% to 65.5% (Liang et al. 2014; Yang et al. 2014b; Yang et al. 2016, 2017). BRWs similarly breed in the study area coinciding with the breeding season of ORWs, and although the breeding density of these two hosts is similar, it is rarely parasitized by CCs (Yang et al. 2022). Experimental design To locate nests of ORWs and BRWs, we systematically searched the reed beds at 3– 5 days intervals from June to August. Most nests were found during building or egg- laying. Once a nest was found, we checked it at 2– 3 days intervals to record the day of clutch completion, the final clutch size and cuckoo parasitism. Recent studies have indicated that the same host can show different rates of rejection for foreign eggs of different colors (Liu et al. 2024; Yan and Liang 2024). Consequently, to examine the anti-parasitism responses of ORWs and BRWs, we placed foreign eggs of different colors into the nests of these two species during the period of egg laying and early incubation. All foreign eggs were commercially sold budgerigar (Melopsittacus undulatus) eggs (2.22 ± 0.12 g in egg mass, 19.56 ± 0.75 mm×15.20 ± 0.78 mm in egg size, n = 30 eggs). These “foreign” eggs were divided into three groups based on color: (1) the red group, in which the surface of the eggs was painted red (Figure 1A and D); (2) the blue group, in which the surface of the eggs was painted blue (Figure 1B and E); and (3) the red together with blue egg group, in which there was a combination of red- and blue-painted eggs (Figure 1C and F). All three groups of foreign eggs were randomly selected for placement in different ORW and BRW nests for experimental assessments. Having placed eggs in all experimental nests, the nests were visited at least once daily to photograph and record the number and types of eggs remaining in each nest. If necessary, a micro-video recorder (Ou Chuang A8; Xiamen Shangyu Huajin Electronic Technology Co., Ltd. Xiamen, China) was used to record the real-time experimental conditions, and behavioral responses were monitored for six consecutive days. Foreign eggs were considered accepted if they remained intact in the nest on day 6, and ORWs and BRWs continued breeding in the nest. Foreign eggs were considered rejected if they were pecked, punctured, buried, abandoned, or even ejected (Moksnes et al. 1991; Yang et al. 2022). The recognition and rejection of foreign parasitic eggs by host birds serves as an effective anti-parasitism strategy, with sympatric hosts exhibiting different rates of egg rejection depending on the level of parasitic pressure. In this study, we conducted egg recognition experiments on the Oriental reed warbler (Acrocephalus orientalis, ORW) and the black-browed reed warbler (Acrocephalus bistrigiceps, BRW), using different colored eggs (red, blue, and red together with blue), with the aim of determining whether there are significant differences between the two host species with respect to the recognition and rejection of eggs. Results revealed that the actual cuckoo parasitism rate differed between the two sympatric breeding hosts, however, ORWs and BRWs are characterized by relatively high rates of egg ejection. Comparisons between the two species with respect to the rejection of eggs in the three different color groups revealed no significant differences, suggesting that both ORW and BRW could recognize and reject foreign eggs at high rates, irrespective of egg color. These findings may thus indicate that although the two sympatric breeding hosts are exposed to different actual risks of cuckoo parasitism, they are both exposed to the same perceived risk of parasitism, and hence are likely to exhibit the similar level of anti-parasitism behavior.